”Sinä iče oled vepsläine, voib sanuda, ka?” : Vepsäläisyyden rakentuminen ja 2000-luvun vepsän kieli - Puura, Ulriikka (Helsingin yliopisto, 2019)
This dissertation consists of four articles and an introductory chapter that describes the background of the study and draws together the main results of the independent articles. The study focuses on the perceptions of speakers of the Veps language on the importance of the Veps language in identifying as a Veps. Veps is a severely endangered language spoken in North-Western Russia in three different administrative areas. Currently there are less than 3,500 mostly elderly bilingual speakers of Veps. Theoretically, this research falls under critical ethnographic sociolinguistics (e.g. Heller & Pietikäinen & Pujolar 2018). Not only does the study discuss the metalanguage of speaking Veps and being Veps, it also foregrounds language ideologies behind these discourses. The language ideologies in turn affect the expectations about language maintenance and revitalization. Further, reflections of bilingualism and language revitalization are analysed in conversational code-switchings of two speakers from the same family. The data consists of Veps speakers’ interviews from 2006‒2011 and of newspaper material from 1993‒2016 from the only Veps language paper Kodima. The interview data are drawn from two research projects, the ELDIA project and the project the Veps language community in the 21st century. The researcher’s field notes were used as ethnographic background data. The study suggests that although the Veps language has been revitalized and standardized since the turn of the 1990s, the discourses of a common Veps ethnic identity have not reached all the speakers. Language endangerment and shift as well as simultaneous language revitalization bring about partly conflicting ideologies and constructions of language and ethnicity. Two different communities are discerned in the data: traditional speakers living in bilingual Veps villages and Veps intelligentsia developing the Veps language in Petrozavodsk, Karelia. The concepts of mother tongue, speakerhood and language acquisition are constructed differently in ...